ANALISIS REKONSILIASI FISKAL ATAS LAPORAN KEUANGAN DALAM MENENTUKAN PAJAK PENGHASILAN BADAN BERDASARKAN UU NO. 7 TAHUN 2021 - Sokya, Iftitah; Zurriah, Rezki (Worksheet : Jurnal Akuntansi, 2025)
This research discusses the fiscal reconciliation analysis of PT Kartika Hijau Lestari's commercial financial reports in determining corporate income tax based on Law no. 7 of 2021. The aim of this research is to determine the suitability of PT Kartika Hijau Lestari's fiscal reconciliation with Law no. 7 of 2021. The types of data used are primary data and secondary data. Data was collected through interview and documentation techniques. The data that has been obtained is then analyzed using descriptive analysis methods. The results of this research indicate that the implementation of fiscal reconciliation at PT Kartika Hijau Lestari is not in accordance with Law no. 7 of 2021.